Mechanochemical synthesis of N-salicylideneaniline: thermosalient effect of polymorphic crystals - Mittapalli, Sudhir; Perumalla, D. Sravanakumar; Nangia, Ashwini (IUCRJ, 2017)
Polymorphs of the dichloro derivative of N-salicylideneaniline exhibit mechanical responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs. The molecules are connected via the amide N-H center dot center dot center dot O dimer synthon and C-Cl center dot center dot center dot O halogen bond in the three crystal structures. A fourth high-temperature Form IV was confirmed by variable-temperature single-crystal X-ray diffraction at 180 degrees C. The behaviour of jumping exhibited by the polymorphic crystals of Forms I and III is due to the layered sheet morphology and the transmission of thermal stress in a single direction, compared with the corrugated sheet structure of Form II such that heat dissipation is more isotropic causing blasting. The role of weak C-Cl center dot center dot center dot O interactions in the thermal response of molecular crystals is discussed.
Keywords: crystal design; crystal engineering; Halogen bonding; hydrogen bonding; intermolecular interactions; materials science; mechanochemistry; polymorphism